Direct Left Atrial Pressure Monitoring in Ambulatory Heart Failure Patients: Initial Experience With a New Permanent Implantable Device - Ritzema, Jay; Melton, Iain C.; Richards, A. Mark; Crozier, Ian G.; Frampton, Chris; Doughty, Robert N.; Whiting, James; Kar, Saibal; Eigler, Neal; Krum, Henry; Abraham, William T.; Troughton, Richard W. (Circulation (New York, N.Y.), 2007)
Background— We describe the first human experience with a permanently implantable, direct left atrial pressure (LAP) monitoring system in ambulatory patients with chronic heart failure. Methods and Results— Eight patients with established heart failure and at least 1 heart failure hospitalization or unplanned visit for parenteral therapy in the last year underwent device implantation under fluoroscopic guidance. All subjects received aspirin 150 mg and clopidogrel 75 mg daily. Subjects measured LAP twice daily and attended a clinic regularly for data upload and device calibration. Right heart catheterization was performed at the time of device implantation and at 12 weeks. The device was implanted in all subjects with no procedural complications. At the 12-week follow-up, 87% of device LAP measurements were within ±5 mm Hg of simultaneous pulmonary capillary wedge pressure readings over a wide range of pressures (1.6 to 71 mm Hg). Net drift corrected by calibration was −0.2±1.9 mm Hg/mo. During short-term follow-up, there were no device-related complications or systemic emboli. There were no deaths, no unplanned heart failure clinic visits, and no admissions for heart failure. Conclusions— Ambulatory monitoring of direct LAP with a new implantable device was well tolerated, feasible, and accurate at a short-term follow-up. Further follow-up and investigation are warranted to evaluate the clinical utility of LAP monitoring in patients with heart failure.